Nodular Regenerative Hyperplasia Secondary to Neoadjuvant Chemotherapy for Colorectal Liver Metastases. (19th November 2009) - van den Broek, Maartje A. J.; Olde Damink, Steven W. M.; Driessen, Ann; Dejong, Cornelis H. C.; Bemelmans, Marc H. A.
Abstract : Liver resection is the only curative treatment for patients with colorectal liver metastases (CLMs). Neoadjuvant chemotherapy can improve resectability but has a potential harmful effect on the nontumorous liver. Patients with chemotherapy-induced hepatic injury undergoing liver surgery have higher risks of post-resectional morbidity. We present two cases of patients without pre-existent liver disease treated with oxaliplatin-based chemotherapy followed by surgical resection of their CLMs. Their intra-operative liver specimen showed morphologic abnormalities characteristic of nodular regenerative hyperplasia (NRH). NRH led to portal hypertension in both patients that resulted in deleterious post-resectional complications and death of one patient. Interestingly, the other patient underwent two repeat nonanatomic liver resections because of recurrent CLMs. The intra-operative liver specimen still showed signs of NRH and sinusoidal congestion, but the post-resectional courses were uneventful. Nevertheless, caution is recommended in patients with suspected NRH. Careful volumetric analysis should guide the operative strategy. When future remnant liver volume is regarded insufficient, portal vein embolization or restrictive surgery should be considered.